PERANCANGAN DATA WAREHOUSE PERPUSTAKAAN - Andri Andri; Baibul Tujni (Direktorat Riset dan Pengabdian Pada Masyarakat (DRPM) Universitas Bina Darma, 2017)
The libraries are the means used to obtain information because the library has a collection that can be used for academicians to obtain information. This study will carry out the design of the data ware house is a repository of data storage in a very large size that is capable of providing subject-oriented database for historical information and can be used to support decision-making system. In this study will be designed a Data Warehouse as a repository library is implemented using software to help Pentaho Kettle. Design of the Data Warehouse in this study using the steps in the development of a Data Warehouse.The results in this study is a draft Data Warehouse is used as a data repository library.